Pelaksanaan Aplikasi SRN PPI dalam Pembinaan Kegiatan Program Kampung Iklim oleh Dinas Lingkungan Hidup dan Pertanahan Sumatera Selatan - Ema, Anggun (Jurnal Studi Pemerintahan dan Akuntabilitas, 2024)
Purpose: This study aims to determine how the application of the national registry system for climate change control is implemented in the climate village program activities by the Department of Environment and Land, South Sumatra Province. Research methodology: The research method used is a qualitative research method. Data collection techniques through observation, interviews, and documentation. Results: The results of this study indicate that the implementation of the national registration system for climate change control in the development of the climate village program by the Department of the Environment and Land of South Sumatra Province has not been fully implemented in the sub-aspects of adaptation and mitigation activities but in the sub-aspects of those responsible for action, information users, registration, validation and leveraging has been done. Implementation: This research was motivated by the existence of problems in implementing the application of the national climate change registration system for the climate village program. Analysis of the implementation of the national registry system for climate change control using indicators according to the Manual of the National Registry System for Climate Change Control, namely the implementing actors, Types and Sources of Action and Implementation Procedures.